English teaching as a community social service to help vulnerable children and teenagers in Chilpancingo de los Bravo, Guerrero, Mexico - Carbajal, Claudio; Castillo, María; Murga, Norma (CIEX JOURNAL, 2020)
Education is an essential human right. In Mexico, 47% of children and teenagers, who are between 3 and 19 years old, do not have access to education, neither do have access to study a foreign language. The main aims of this research are to create awareness and to show the advantages of social service to reduce the disadvantages of vulnerable students when learning English. In order to achieve these aims, a mixed approach was used with a qualitative dominant model. Thus, quantitative, as well as qualitative information was necessary to gather better results. Action research was used as research method, since this method essentially promotes the social change, transforms the reality, and make people conscious in transformative processes. The results highlighted the difference that pre-service teachers could make if they apply social service to help vulnerable sectors of the community. Concluding that social service is one of the keys to solve community problems.